2018
DOI: 10.1098/rstb.2017.0317
|View full text |Cite
|
Sign up to set email alerts
|

Blocking mechanosensitive ion channels eliminates the effects of applied mechanical loading on chick joint morphogenesis

Abstract: Abnormalities in joint shape are increasingly considered a critical risk factor for developing osteoarthritis in life. It has been shown that mechanical forces during prenatal development, particularly those due to fetal movements, play a fundamental role in joint morphogenesis. However, how mechanical stimuli are sensed or transduced in developing joint tissues is unclear. Stretch-activated and voltage-gated calcium ion channels have been shown to be involved in the mechanoregulation of chondrocytes in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…This in vivo recovery supports the conclusions of in vitro tissue explant models, in which externally applied movements affect the shapes of developing limb rudiments. 18,19,24 Our results demonstrate that shape at e9 is tightly linked with successful cavitation, as previously proposed. 9 When cavitation was consistently classified as normal (most notably in the single-day paralysis group), there were limited effects on joint shape compared to controls, whilst when cavitation was consistently absent in the I3-8, I4-8, and I5-8 sustained paralysis groups, all aspects of joint shape measured were substantially decreased relative to controls (Figures 2 and 4).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This in vivo recovery supports the conclusions of in vitro tissue explant models, in which externally applied movements affect the shapes of developing limb rudiments. 18,19,24 Our results demonstrate that shape at e9 is tightly linked with successful cavitation, as previously proposed. 9 When cavitation was consistently classified as normal (most notably in the single-day paralysis group), there were limited effects on joint shape compared to controls, whilst when cavitation was consistently absent in the I3-8, I4-8, and I5-8 sustained paralysis groups, all aspects of joint shape measured were substantially decreased relative to controls (Figures 2 and 4).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, a severe reduction in early whole‐body movements can be compensated for to some degree by applied, localized movements. This in vivo recovery supports the conclusions of in vitro tissue explant models, in which externally applied movements affect the shapes of developing limb rudiments 18,19,24 …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Several studies have reported that ion channels residing in the plasma membrane of chondrocytes and osteoblasts are involved in the transduction of mechanical signals [7][8][9]. The existence of ENaC in load-bearing cells suggests that ENaC has a mechanoactive role in cellular signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Each cell was stained with Hoechst (blue) to reveal the nucleus, and the images were merged with the corresponding fibronectin or N-cadherin (green). S -: no mechanical stimulation; S + : cyclic stretching applied; B -: no benzamil; B + : with ENaC inhibitor, benzamil 8. Stem Cells International which in turn phosphorylates C-Jun leading to an increased transcriptional activity.…”
mentioning
confidence: 99%